EVALUASI KEAMANAN AKSES JARINGAN KOMPUTER NIRKABEL (KASUS : KANTOR PUSAT FAKULTAS TEKNIK UNIVERSITAS GADJAH MADA) - , IDA BAGUS VERRY HENDRAWAN MANUABA ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The growth of computer network either wired or wireless networks are currently experiencing an increase that can be said very fast .. The growth of information technology and telecommunications technology seemed to be a converged network that caused so much development and the demands of users. This requires interoperability, joint arrangements and various solutions to increasingly complex problems such as computer network security issues, especially the wireless computer network security. Evaluation is needed to keep a step back and assess the stability of the system to remain adequate. One way to evaluate a wireless computer network is to penetrate the system that has been running with all forms of attacks trying to find security holes. Evaluation is done in a systematic, periodic and objective of the relevance, performance and success of ongoing activities or which have been resolved against the concept, design, implementation, and produce benefits. The study produced a model of wireless network security as a result of evaluation that can be used as a useful input to improve the security of access to wireless networks that impact on performance on the network located at the Central Office of Engineering Faculty of Gadjah Mada University